A Strategy of Transparent Conductive Oxide for UV Focal Plane Array Detector: Two‐Step Thermodynamic Process. (4th October 2016) - Zhang, Dan; Zheng, Wei; Zheng, Qinghong; Chen, Anqi; Ji, Xu; Huang, Feng
Abstract : A deep UV transparent Al:Mg0.43 Zn0.57 O (AMZO) film with high electrical conductivity (406.6 S cm −1 ) and high UV light transmittance is prepared via a designed two‐step method controlling the thermodynamic process of doping. The method proposed here can provide a reference for the production of deep UV luminescent materials.